Comparison of Postoperative Sore Throat and Hoarseness Between Two Different Sizes of Endotracheal Tube in Females after General Anesthesia - Abdul Rehman, Waqas Anjum, Hasham Bin Ghafoor, Zille Huma Zeb, Abeera Zareen, Muhammad Waqas, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the frequency of postoperative sore throat and hoarseness between two different sizes of endotracheal tube in females after GA. Material and Methods: It was comparative analysis study carried in Anaesthesia Department, QIH, Islamabad. During study 200 patients were included (100 patients in each group) according to inclusion criteria. All data was entered in computer software SPSS version 24.0. Results: Mean age of the patients in Group-A (ETT size 6.0 mm) was 42.2 ± 15 years and 46.7 ± 13.1 in Group-B (ETT size 7.0 mm). The mean duration of surgery among the patients was 57.90 ± 19.8 minutes in Group-A and 77.4 ± 42.2 minutes in Group-B. In Group-A nasogastric tube was used among 36 patients while in Group-B it was used among 25 patients. In both groups, throat pack was not used for any patient. In Group-A, 96 patients and in Group-B, 55 patients had no sore throat. None of the patients in both groups had hoarseness of voice after the procedure. Conclusion: Study concluded that there was significant difference in the mean score of sore throat when ETT of two different sizes were used. ETT size 6.0mm significantly reduces the incidence of sore throat among females after GA. Keywords: Incidence, sore throat, endotracheal tube, intubation.